The Effect of Sigembul Innovation (Mother Action Care on the Health of Together) on the Reduction of Stunting Cases in Olak-Olak Village, Kubu in 2021 - Kosmiati Kosmiati; Novita Novita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Data on stunting in Indonesia is considered very high, although it is decreasing compared to 2012. Based on UNICEF estimates (31.8%) children experience stunting in Indonesia, thus achieving the very high predicate (very high). With this figure, Indonesia ranks higher than South Korea (2.2%), Japan (5.5%), Malaysia (20.9%), China (4.7%), Thailand (12.3%), Philippines (28.7%), and Kenya (19.4%). Even so, the percentage of stunting in Indonesia is lower than in Congo (40.8%), Ethiopia (35.3%), and Rwanda (32.6%). More intensive efforts will be needed if the world is to achieve the global target of reducing stunting children to 104 million by 2025, and to 87 million by 2030 ( UNICEF, 2021) Method: The research method used is a quantitative type of research which uses a questionnaire data collection technique, the sample in this research is 72 toddlers. Result: SIGEMBUL's innovation flow in reducing stunting rates in Olak-Olak Kubu Village is by creating a whatsapp group which is followed by collecting data on toddlers who do not come to the posyandu then informing mothers of toddlers regarding the names of those who are not present at posyandu via whatsapp group, then mother together with the Balit, they come to the residence of the midwife/cadre to measure and weigh body weight. After that, it was continued by sending the results of the toddler's measurement to the SIGEMBUL whatsapp group and the posyandu cadre doing the recording of the toddler's measurement data, lastly, the posyandu cadre reporting the measurement results of the required agencies (villages and health centers). Conclusion: The result of a significance value of 0.000 means Ha is accepted and H0 is rejected so it can be concluded that there is an effect of sigembul innovation (Action for Mothers Care for Scales and Toddler Health) on the reduction of stunting cases in Olak-olak Kubu Village.